Presence of hyperalgesia predicts analgesic efficacy of topically applied capsaicin 8% in patients with peripheral neuropathic pain. (8th April 2015) - Mainka, T.; Malewicz, N.M.; Baron, R.; Enax‐Krumova, E.K.; Treede, R.‐D.; Maier, C.
Abstract: Background: Topical high‐dose capsaicin acting on TRPV1 receptors and inducing an intraepidermal decrease in the small nerve fibre count is effective in treating neuropathic pain (NP). Sensory changes after capsaicin application, their correlation with pain relief and their role as possible predictors of response have been insufficiently analysed. We hypothesized a positive correlation between pain relief and increase in the warmth detection threshold (WDT), indicating loss of C‐fibre function, and higher response rates in patients with preserved C‐fibre function or heat hyperalgesia before application. Methods: Quantitative Sensory Testing (DFNS protocol) was conducted in 20 unilaterally treated patients with peripheral NP (peripheral nerve injury: n = 14, polyneuropathy: n = 4, postherpetic neuralgia: n = 2) before and 2, 4, 6 and 8 weeks after application of capsaicin (8%) in this open‐label study. Response was defined as ≥30% or ≥2 (Numeric Rating Scale: 0–10) decrease of current pain at any follow‐up compared to baseline. Results: In all patients, WDT significantly increased 8 weeks after capsaicin application, but did not correlate with pain relief in responders ( n = 10, r = 0.179, p = 0.141). Before treatment, responders showed significantly higher z ‐values for the cold (CPT, +0.7 ± 1.1 vs. −0.4 ± 0.9) and mechanical pain threshold (MPT; 0.7 ± 2.5 vs. −1.2 ± 1.3), but did not differ from non‐responders regarding WDT or heat pain threshold. A sum of the z‐values for CPT and MPT >0.8 before treatment identified responders with 100% specificity and 70% sensitivity. Conclusions: Efficacy of capsaicin does not correlate with the induced loss of function of small fibres, measured by QST. Presence of cold and pinprick hyperalgesia seems to be predictive of response to capsaicin (8%).